Effect of the Crosslinking Between the Asphalt and Polyethylene on the Viscoelastic Properties of Polyethylene Melt Extruding Through Capillary - M. Naeem, Mostafa; N. Khalaf, Moayad; Abd-Alkarem, Hashmya; Abd-Alhasan, Mazen (University of Thi-Qar Journal of Science, 2019)
The viscoelastic properties of polyethylene were studied with different percent of asphalt (1%,3%,5%,7% and 10% ) and 1% of organic peroxide as crosslinking agent. The data shows that the 1% of asphalt loading in the polymer decrease the shear stress and viscosity of the matrix polymer in all the test temperature (170,190,210 and 230oC) .The best percent of asphalt that gives controlled crosslinking between the polymer chains was 1% asphalt loading, while higher asphalt percent will increase the chain entanglements .